Positive aspects of old age in University of Third Age students’ perception - Wawrzyniak, Joanna; Woźnicka, Elżbieta (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Article refers to general perception of old age as a period characterized negatively. Nowadays old person andor pensioner is a person with low prestige in society, old age is recognized as sad period, useless, unsatisfying. Authors present results of research carried among participants of Universities of Third Age about their own perception of old age in a positive context. Authors analyze the statements (opinions) of students using the positive psychology and conditions of satisfaction, that subjectively describe old age as positive phase of life. Conclusions from that research give us important facts about adult education as well as gerontology prevention.